Investigating the effect of motivation for attendance and quality of services on spectator satisfaction in Ardabil Province World Men's Volleyball League (2019) - Samin Mehrinejad Khotbesara; Mehrdad Moharramzadeh (Research in Sport Management and Marketing)
Purpose:  Spectators, like athletes, are the main customers of sports whose motivation to participate in sports competitions is very important.Methods: It was a descriptive study and the statistical population included all spectators who were watching the 2019 Men's Volleyball Nations League matches in Rezazadeh Ardabil sports complex. According to Morgan table, 384 people were included in the statistical sample. The research tool was a questionnaire whose validity was approved by 10 professors of sports management and its reliability was calculated by Cronbach's alpha test to be 0.68 for the spectators’ motivation questionnaire and 0.7 for the satisfaction questionnaire.Results : The results showed that the motivational factors of team identity, victory and pleasure and the factor of technical and executive position were the most important aspects of spectators' motivation to participate. Although there was a significant relationship between all dimensions of motivation and spectators' satisfaction, team loyalty, interest and access were highly correlated with spectators' satisfaction.Conclusion: A positive and significant relationship between all dimensions of motivation and spectators 'satisfaction showed that the more motivational factors are strengthened and the setting for the spectators' presence is provided and prepared, they will be more satisfied and the possibility of their re-presence will be higher.